MODEL FORMATION REQUIREMENTS FOR AUTOMOBILE CHECKPOINT STRUCTURE IN THE CONDITIONS OF IMPLEMENTING THE CONCEPT OF INTEGRATED BORDER MANAGEMENT - Gorodnov, V. P.; Kyrylenko V. А.; Petrov V. М. (Honor and Law, 2019)
The article presents a model of the automobile checkpoint requirements structure in the conditions of the integrated border management concept implementation, which allows you to implement operational control of the automobile checkpoint structure in tasks of border control in the dynamics of unpredictable changes people and vehicles flows intensity.